Spectrum of coagulation profiles in severely injured patients: A subgroup analysis from the FIRST ( Fluids in Resuscitation of Severe Trauma) trial - Nathire, Mohammad El Hassed (Division of General Surgery, 2022)
Background: Uncontrolled bleeding accounts for the majority of preventable deaths in the severely injured in both the civilian and military settings. Trauma induced coagulopathy (TIC) is now widely accepted as a major contributing factor to worsening bleeding in these patients. A quarter of severe trauma patients present with coagulopathy on admission and remain a group with high morbidity and mortality. Objectives: To describe the spectrum of coagulation profiles amongst severely injured patients presenting to an urban level-one trauma centre at Groote Schuur Hospital and to correlate these with blood product requirements, morbidity and mortality. Method: This is a retrospective study of all patients with complete baseline TEG coagulation parameters collected prior to randomization in the FIRST (Fluids In Resuscitation of Severe Trauma) trial between January 2007 and December 2009. Parameters recorded for this study included patient demographics, mechanism of injury, admission vital signs, lactate, base excess, coagulation studies PT, INR, TEG parameters, volume and type of fluids administered, volume of blood products administered, length of ICU stay, and major outcomes. Injury severity was categorized according to the Injury Severity Score (ISS) and New Injury Severity Score (NISS). Results: A total of 87 patients were included in this study, with a median ISS of 20 and 57.5% had a penetrating injury mechanism. Coagulopathy was highly prevalent in this cohort, of which a majority (69%) was diagnosed with hypercoagulopathy and 24% had a hypocoagulopathy status on admission. There was no difference in age, gender and amount 9 of pre-hospital fluids administered across the three groups (normal v/s hyper v/s hypo). Median volume of blood products was higher in the hypocoagulopathy group, although not statistically significant. Overall, 30-day mortality rate was 13%, with case fatalities occurring in only coagulopathic patients; hypercoagulopathy (15%) and hypocoagulopathy (10%). Conclusion: Trauma induced coagulopathy is not an infrequent diagnosis and remains a challenging clinical entity to manage in severely injured patients resulting in increased morbidity and mortality. Determining the coagulation profile using TEG at presentation in this group of patients may guide appropriate management guidelines in order to improve outcome. Hypercoagulable patients need to be recognised amongst the TIC patients as it results in different sequelae and impacts on clinical decision in the use of antifibrinolytic agents as compared to hypocoagulopathy.